Tajfif Manabi’ Takfir Ahl Islam - Imdad Rabbani (Universitas Darussalam Gontor, 2017)
Throughout extended period of Islamic history, takfir among Muslims has been common practice whenever sectarian discord happens. Advancement of information technology today, especially social media, often reinforces this tendency. Voices based on scientific and objective study on such particular action and view to be deemed outside Islam and its committer as kafir are almost unheard of, or at least not given due attention. What is in vogue emotional outlook inspired by shallow fanaticism and boosted by decentralized public communication channels, which enable virtually anybody, even those with no authority, to comment on this issue. Therefore, it is imperative to examine views of ulama concerning this subject to provide Muslims with better equipment to respond to similar instances, whenever they might happen. This short paper is aimed at humbly contributing in this discussion, by presenting authoritative view of ulama coming from different scientific tradition concerning this debate. What is discussesd is definition of takfir and its context; how someone becomes Muslim and prohibition on declaring a Muslim kafir; some verses from Al-Quran and narrations of Prophetic Tradition which seem to call some major sinners to be kafirs and views of ulama on such verses and narrations; discussion on what may lead to justified takfir, i.e, violation of the two declarations of faith; and attitude to be adopted by contemporary Muslim. Among conclusion of this paper is the importance of cautious measure to declare kafir someone who already makes two declarations of faith, regardless of the motive.